Kynurenine pathway metabolites are associated with gray matter volume in subjects with schizophrenia - Zhou, Sumiao; Huang, Yuanyuan; Kuang, Qijie; Yan, Su; Li, Hehua; Wu, Kai; Wu, Fengchun; Huang, Xingbing (Frontiers in Psychiatry, 2022)
Background: There has been growing evidence of the existence of abnormalities in the kynurenine pathway (KP) and structural grey matter volume (GMV) in schizophrenia (SCZ). Numerous studies have suggested that abnormal kynurenine metabolism (KM) in the brain is clearly associated with the pathogenesis of schizophrenia and may be one of the pathological mechanisms of SCZ. In this pilot study, we investigated whether there was a correlation between KP and GMV in schizophrenia patients. Methods: The plasma levels of KM were measured in 41 patients who met the Structured Clinical Interview of the Diagnostic IV criteria for schizophrenia and 60 healthy controls by using liquid chromatography-tandem mass spectrometry, and cortical thickness (as measured via magnetic resonance imaging) was obtained. Results: Our study showed no statistically significant differences in the concentrations of kynurenine (KYN), tryptophan (TRP), and KYNA/TRP (all p > 0.05), but kynurenic acid (KYNA) and the KYNA/KYN ratio were significantly higher in the schizophrenia subjects than in the healthy controls (F=4.750, p=0.032; F=6.153, p=0.015, respectively) after controlling for age and sex. Spearman’s tests showed that KYN concentrations in SCZ patients were negatively correlated with GMV in the left front cingulate belt (r=-0.325, p=0.046) and that KYN/TRP was negatively correlated with GMV in the left island (r=-0.396, p=0.014) and right island (r=-0.385, p=0.017). Conclusion: Our findings appear to provide new insights into the predisposition of an imbalance in the relative metabolism of KYN/TRP and KYN to GMV in schizophrenia.